The Effectiveness of Oketani Massage on the Prevention of Mother’s Breast Milk Dam ASI on Postpartum and Post Sectio Sesarea - Tiarnida Nababan; Wicak Tini Hia; Nia Rahmawi; Triana Anggreni Haloho; Yenni Anita Hutagalung (Jurnal Penelitian Perawat Profesional, 2020)
Lactation failured were often the resulted of several lactation problems, one of that problem was breast milk dam. Oketani massage was one of the methods of breast treatment that caused pectoralist muscle forces to increased breast milk production, fixed problems lactation as well as and easier for a baby to sucked milk. The purposed of these studied was to know the effectiveness of Oketani massage on the prevention of mother’s breast milk dam on postpartum and the post sectio sesarea. The design of these studied used a pre experiment design or a pre design for post test only design or the one shot case study. The case studied was conducted on June 19 to July 02, 2020 with 233 of population and 35 respondents of subject. The data-gathering technique used observation sheet with bivariates. Research showed that all of respondents (100%) were not on breast milk dam and their breast milk production was increased. Data analysis results obtained z value=-4,472 compounds and the p-value=0,000 with a degree of significance p<0.05. The conclusion of the studied states that the breast milk dam on postpartum and the post secsio sesarea wa 100% effectively preventabled with an Oketani massage. The researchers suggested the medical staff that Oketani massage are highly recommended to switched from traditional breast treatment to current breast treatment, besides been effective to prevented breast dam, it also increased breast milk production.